2010
DOI: 10.1007/s00296-010-1636-6
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma level of HMGB1 is associated with disease activity and combined alterations with IFN-alpha and TNF-alpha in systemic lupus erythematosus

Abstract: Recent studies indicate that high-mobility group box protein 1 (HMGB1) contributes to the pathogenesis of diverse autoimmune disorders. It induces the production of interferon-alpha (IFN-alpha) and tumor necrosis factor alpha (TNF-alpha) in vitro. In the present study, plasma HMGB1, TNF-alpha, and IFN-alpha were determined with ELISA in 37 patients with systemic lupus erythematosus (SLE) and 39 age- and sex-matched healthy controls (HC). The possible associations of these cytokines with disease activities, aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
65
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 38 publications
12
65
0
1
Order By: Relevance
“…[16] Some studies have reported a relationship between the high serum level of HMGB1 and flare-ups of lupus disease activity. [17,18] All of these observations support the notion that the HMBG1-RAGE pathway plays a part in the pathogenesis of SLE.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…[16] Some studies have reported a relationship between the high serum level of HMGB1 and flare-ups of lupus disease activity. [17,18] All of these observations support the notion that the HMBG1-RAGE pathway plays a part in the pathogenesis of SLE.…”
supporting
confidence: 75%
“…[37] Studies have shown that the HMGB1 plasma level, one of the main RAGE ligands, is increased in the circulation of SLE, leading to the binding and consumption of sRAGE during the inflammatory process. [18,38] Another possible regulatory route of the sRAGE level is through alternative splicing and proteinases. Zong et al [39] recently proposed that sRAGE might not only function as a 'decoy' to exert its inhibitory effects on RAGE but also act in a more direct way by binding to the cell surface of RAGE to block the formation of homodimers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in experimental systems, depletion of neutrophils can protect against antibody-mediated glomerulonephritis (56) and lupus serum from human patients can induce neutrophil-mediated organ damage (57). The presence of neutrophilic infiltrates has been recognized as an early feature of glomerulonephritis (58, 59), while proteins released from neutrophilic granules are toxic to glomerular structures (59-61) and circulate at elevated levels in the blood (62)(63)(64). To these previous observations, a role has recently been hypothesized for NET formation in the pathogenesis of -and organ damage associated with -SLE (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…10 In SLE patients, HMGB1-nucleic acids complexes are released from secondary necrotic cells and forms ICs with the corresponding autoantibodies, which are significantly elevated in the sera. 1,3,10,11 Depositon of HMGB1-containing ICs are also found in target tissues, such as the skin 12 and kidney, 13 where they contribute to both chronic inflammation and tissue injury. The proinflammatory activity of HMGB1 is mostly attributed to its ligation with RAGE, 14 which is a member of the immunoglobulin superfamily of cell surface molecules.…”
mentioning
confidence: 99%